Immunosensor for diagnosis of Alzheimer disease using amyloid-β 1-40 peptide and silk fibroin thin films - Gonçalves, J. M. [UNESP]; Lima, L. R. [UNESP]; Moraes, M. L.; Ribeiro, S. J.L. [UNESP] (Elsevier, 2016)
Layer-by-Layer (LbL) films containing silk fibroin (SF) and the 40 aminoacid-long amyloid-β peptide (Aβ1-40) were prepared with the purpose of developing a new prototype of an electrochemical immunosensor. The film showed a satisfactory growth in quartz substrate and screen-printed carbon electrodes, as observed by UV-vis spectroscopy and cyclic voltammetric, respectively. The peptide immobilized in LbL films in junction with SF shows secondary structure induced, as shown by circular dichroism measurements, favoring the interaction SF/peptide LbL film with the specific antibody. Immunosensor showed a linear response in the presence of the antibody with concentrations from 0 to 10 ng mL- 1 both analyzed by current changes in 0.3 V and voltammogram area. This system can be applied as a new prototype for preliminary diagnosis of Alzheimer's disease.
Keywords: Alzheimer's disease; Amyloid-β peptide; Immunosensor; Layer-by-layer; Silk fibroin